Otwarte kody źródłowe i moda - Raciniewska, Alicja (Człowiek i Społeczeństwo, 2015)
The impact of the Internet and digital technologies on the contemporary fashion system is undeniable and evident in almost every aspect of its operation – in the techniques of design, material production, sales and distribution, methods of communication, consumption and, finally, the fashion education. There is no place to discuss all these areas in this article, so therefore, I will focus on the issue relatively poorly discussed in our country, which is the application of the open source philosophy in fashion. In the first part of this article the most important assumptions of the open source movement is presented. The second discusses the most important actors and practices of open source in fashion. The final part of the article is devoted to the evaluation of the analyzed phenomenon.